The New International Chambers of the Paris Courts - Innovative Way for Resolution of Commercial Disputes - Kocev, Ljuben (Institute of Knowledge Management, Skopje, 2018)
The process of the withdrawal of the United Kingdom form the European Union has been discussed predominantly from a political and economic point of view. However, the consequences are more far reaching. With UK on the doorstep of leaving the EU, the decisions issued by its courts would no longer benefit from the recognition system provided in the Brussels Regulation (Council Regulation (EC) No. 44/2001). As a result of this, it is expected that London would no longer be seen as a primary destination for international litigants. In the awaiting of the aftermath from the Brexit, other cities and member state countries of the EU have started the race to position themselves as the next “legal hub”. While other member states have been vocal about offering alternative courts, so far France has been at the forefront of this initiative. On 7 February 2018 two Protocols were signed by the French Minister of Justice, the President of the Paris Bar, and the presidents of the Paris Court of Appeal and the Paris Commercial Court. With the first protocol amendments were made to the already existing International Chamber within the Paris Commercial Court, whereas with the second Protocol a new International Chamber has been created within the Paris Court of Appeal. The aim of the creation of these international divisions within the Paris Court is to create an attractive jurisdictional system which would meet the expectations of the economic actors. Paris has already been one of the most important world centers for dispute resolution as a result of the work of the International Chamber of Commerce and its work in the field of Alternative Dispute Resolution (ADR). However, with this initiative Paris has an opportunity to further strengthen its attractiveness. The adoption of the two Protocols is a groundbreaking move which sets forth innovative rules of procedure, incorporating unique approaches in the field of international commercial litigation. The rules of procedure contain an increased level of flexibility offering the parties a chance for litigations with great similarity to arbitration. Most notably, the new Protocols provide for the usage of English as language in the course of the proceedings, adapted procedure which should better suit the need of the parties, focus on oral testimonies instead of written witness and expert submissions, possibility for cross – examination, broader scope of tools for securing evidence, such as requests for document production, as well as the possibility of non- French lawyers to appear in front of the Courts. The aim of this article is to provide an insight in the new structure of the International Chambers by reviewing the novelties in the two new Protocols. The article reflects on similar initiatives which have been undertaken in other EU members and countries worldwide, and whether this can be the starting point for more drastic and revolutionary reforms in the traditional litigation system.
Keywords: Specialized commercial courts, Commercial law, International Commercial Chambers, Dispute resolution.